Wide spectrum of tick-borne pathogens in juvenile Ixodes ricinus collected from autumn-migrating birds in the Vistula River Valley, Poland - Kulisz, Joanna; Zając, Zbigniew; Foucault-Simonin, Angelique; Woźniak, Aneta; Filipiuk, Maciej; Kloskowski, Janusz; Rudolf, Robert; Corduneanu, Alexandra; Bartosik, Katarzyna; Moutailler, Sara; Cabezas-Cruz, Alejandro (BMC veterinary research, 2024)
Migratory birds serve as potential hosts for ticks and can be reservoirs of tick-borne pathogens (TBPs). The aim of our study was to investigate the prevalence of TBPs in juvenile Ixodes ricinus collected from Erithacus rubecula, Turdus merula, and Turdus philomelos passing through the Vistula River Valley, Poland - one of the most important European north-south routes for migratory birds. To detect TBPs in collected ticks we used a high-throughput microfluidic real-time PCR method. In addition, we performed a phylogenetic analysis of Borreliella garinii flaB and Rickettsia helvetica ompB sequences, considering haplotype diversity through a Median Joining Network. Our results showed a high prevalence and wide spectrum of TBPs in both larvae and nymphs of I. ricinus. Overall, including co-infections, 47.41% of the tested tick specimens were infected with at least one TBP. Borreliaceae spirochetes were detected in ticks collected from all examined bird species. Ticks (larvae and nymphs) collected from T. merula showed the highest prevalence of Bo. garinii (33.33%), Bo. burgdorferi s.s. (7.69%) and Borrelia miyamotoi (2.56%), while the highest number of ticks infected with Bo. valaisiana were collected from T. philomelos (8.11%). In turn, the highest prevalence of R. helvetica (20.00%) was observed in ticks collected from E. rubecula. Additionally, infections with A. phagocytophilum (5.00%), Ehrlichia spp. (2.50%), Ba. divergens (2.50%) and Ba. venatorum (2.50%) were only confirmed in ticks collected from this bird species. The phylogenetic analysis of Bo. garinii revealed that the detected haplotype circulates widely across various hosts and is geographically widespread, while the haplotype of R. helvetica is mainly detected in ticks in Central Europe. Ticks carried by T. merula, T. philomelos, and E. rubecula migrating along the Vistula River Valley, Poland are characterized by a high prevalence and a wide spectrum of detected TBPs. Tested ticks carry widespread strains of Bo. garinii, in contrast to R. helvetica, which is mainly found in Central Europe. Therefore, further research on the possible role of birds as reservoirs of TBPs is needed.